Protocol to study the neural mechanism of music therapy in alleviating depression using EEG-LFP signal recording - Lin, Qixuan; Cao, Yu; Wu, Yunhao; Qiu, Xian; Sun, Bomin; Lv, Xin (STAR protocols, 2025)
Here, we present a protocol for studying the neural mechanism of music therapy in alleviating depression using a combined electroencephalogram (EEG) and local field potential (LFP) signal recording. We describe steps for subject recruitment, surgery for implanting recording devices, signal processing, and emotional assessments. We then detail procedures for recording and analyzing EEG and LFP data. This protocol focuses on understanding how personal music preferences contribute to the therapeutic benefits of music in treating psychiatric conditions. For complete details on the use and execution of this protocol, please refer to Lv et al.1 [Display omitted] •Music therapy design with the control of multiple factors•EEG-LFP-physio-signal data recording and preprocessing•Analysis of neural oscillations and temporal coupling•Auditory entrainment and clinical assessment Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics. Here, we present a protocol for studying the neural mechanism of music therapy in alleviating depression using a combined electroencephalogram (EEG) and local field potential (LFP) signal recording. We describe steps for subject recruitment, surgery for implanting recording devices, signal processing, and emotional assessments. We then detail procedures for recording and analyzing EEG and LFP data. This protocol focuses on understanding how personal music preferences contribute to the therapeutic benefits of music in treating psychiatric conditions.